2021
DOI: 10.1007/s43545-021-00145-2
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment and disengagement: two sides of the same coin or different phenomena?

Abstract: We investigate the disengagement of four former activists of the Landless Rural Workers Movement (Movimento dos Trabalhadores Rurais Sem Terra—MST) in Brazil. The MST is the largest Brazilian social movement and has mobilized activists for over 30 years. The trajectories of recruitment, participation and disengagement of its activists serve as emblematic cases for the study of disengagement in social movements in general. This research contributes to the understanding of the activists’ disengagement from a soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…The analysis of most studies in the literature rests on the assumption that political engagement is voluntary and the choice of adult individuals. Yet, this is not always true (especially in the Global South), as some empirical studies demonstrate (Nascimento et al, 2021;Viterna, 2006). Are the disengagement pathways in these cases dissimilar?…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The analysis of most studies in the literature rests on the assumption that political engagement is voluntary and the choice of adult individuals. Yet, this is not always true (especially in the Global South), as some empirical studies demonstrate (Nascimento et al, 2021;Viterna, 2006). Are the disengagement pathways in these cases dissimilar?…”
Section: Discussionmentioning
confidence: 99%
“…Both the formation and maintenance of collective identities require continuous identity work throughout the different stages of a movement to accomplish the alignment of personal and collective identities (Snow and McAdam, 2000). If this alignment weakens, then disengagement is a potential outcome (Nascimento et al, 2021). The process of collective identity construction is very complex since the multiple and intersecting identities (in terms of class, gender, race, ethnicity, sexuality, citizenship status, etc.)…”
Section: Identitymentioning
confidence: 99%
See 1 more Smart Citation
“…Disengagement or demobilization is one of the understudied areas in social movement research, presumably due to the methodological limitation of reaching out to ex‐activists (Fillieule, 2014). Some examine disengagement as one type of movement behavior (Corrigall‐Brown, 2011), while others investigate individuals' paths or trajectories to disengagement in a process model (Fillieule, 2014; Klandermans, 1997; Nascimento, Klandermans, & de Theije, 2021; White, 2010). For instance, Nascimento et al.…”
Section: Disengagementmentioning
confidence: 99%
“…For instance, Nascimento et al. (2021) examined the process through which long‐term participants of the Landless Rural Workers Movement in Brazil eventually left the movement. They found that disengagement was an outcome of multiple reasons related to one's personal and social characteristics, creating different paths for individual disaffiliation.…”
Section: Disengagementmentioning
confidence: 99%